ENGLISH RELATIVE PRONOUNS COMPARED TO THOSE OF ARABIC :A Descriptive Study of English and Arabic Relative Pronouns in the English Translation of Qur'anic Verses - Lela Awaliyah, - (2008)
This research entitled "EnglishRelative Pronouns Compared to Those of Arabic (A Descriptive Study of English and Arabic Relative Pronouns in the English Translation of Qur'anic Verses)" is aimed to investigate the similarities and differences between English and Arabic relative pronouns in selected Qur'anic verses in terms ofsyntactic functions. This research draws upon verses in Surah An-Nisaa (The Women) as the main samples and other verses as supporting samples. To conduct this research, a qualitative was used, involving descriptive research method andcontent analysis. The findmgs show that similarities between English and Arabic relative pronouns are in their definitions, syntactic patterns of word order and translations. However, these two languages differ significantly in category of number, the presence or absence ofgrammatical gender with respect to the way the relative pronouns are marked In terms of position ofhead noun, English relative pronouns need to agree with the head noun it replaces, while Arabic follows the head noun that need to agree with the head noun in case. The difference is also obvious in terms ofthe presence or absence ofa pronominal reflexive. English does not allow pronoun retention as the object and object of preposition, while Arabic retains the object and object of preposition. This research concludes that the strategies ofrelativization used by the two languages are different. The strategy used in English is relative pronouns, while Arabic employs pronoun retention strategy.